2016
DOI: 10.1111/febs.13695
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 enhances the effect of BMSCs on extracellular matrix remodeling in a rabbit model of intervertebral disc degeneration

Abstract: Intervertebral discs (IVDs) provide stability and flexibility to the spinal column; however, IVDs, and in particular the nucleus pulposus (NP), undergo a degenerative process characterized by changes in the disc extracellular matrix (ECM), decreased cell viability, and reduced synthesis of proteoglycan and type II collagen. Here, we investigated the efficacy and feasibility of stem cell therapy using bone marrow mesenchymal stem cells (BMSCs) over-expressing bone morphogenetic protein 7 (BMP7) to promote ECM r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…To remedy the low amount of cells present, a combination of BMPs and MSCs could further augment IVD regeneration. In this scenario, BMPs are expected to both stimulate the resident NPs to proliferate and produce the matrix and facilitate MSCs to enter the chondrogenic lineage [34].…”
Section: Introductionmentioning
confidence: 99%
“…To remedy the low amount of cells present, a combination of BMPs and MSCs could further augment IVD regeneration. In this scenario, BMPs are expected to both stimulate the resident NPs to proliferate and produce the matrix and facilitate MSCs to enter the chondrogenic lineage [34].…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of BMP-7 expressing cells has been performed for DD models as BMP-7 exerts chondrogenic effects and is known to stimulate anabolic effects in disc cells too. 121,122 These studies demonstrated improved morphology and tissue content measured months after delivery in rodent and rabbit DD models, indicating potential longer term effects with this approach. 121,122 Other lesser known factors have also been utilized that induce desired musculoskeletal phenotypes.…”
Section: Gene-engineered Stem Cellsmentioning
confidence: 82%
“…121,122 These studies demonstrated improved morphology and tissue content measured months after delivery in rodent and rabbit DD models, indicating potential longer term effects with this approach. 121,122 Other lesser known factors have also been utilized that induce desired musculoskeletal phenotypes. Overexpression of NELL-1 has been utilized to improve repair of osteochondral defects as NELL-1 is known to induce stem cells down an osteochondral lineage.…”
Section: Gene-engineered Stem Cellsmentioning
confidence: 82%
“…Consequently, BMP‐7 injection has been utilized to treat IVD degeneration in various animal models, including rabbits and canines . Xu et al observed that the implantation of MSCs overexpressing BMP‐7 promotes cell differentiation and proliferation in the nucleus pulposus. In the current study, we showed that injecting hypoxic MSCs resulted in the upregulation of disc BMP‐7 expression as compared to that in discs injected with normoxic MSCs.…”
Section: Discussionmentioning
confidence: 99%